Preparation of Artificial Diets to Barbus xanthopterus larvae and Juveniles - Yesser, Abdulkareem T.; Al-Katrani, Layla M A.A.; Younis, Kadhum H.; Farnar, Khaled W; Al-Hamdany, Qusy H. (Iraqi Journal of Aquaculture, 2016)
The study was aimed to prepare artificial diets from local ingredient to larvae and juveniles of Barbus xanthopterus, in order to examine its ability to eat dry food as a substitute to the expensive live food and study its effects on survival and growth rates. Four types of diets were processed to larvae which were: standard artificial diet as a control T1, fish meal diet T2, starter diet T4 and egg and milk mixture diet T3. Two additional diets were used for juveniles as well as the control diet which were crumbles and pellets. Aquaria and cages were employed to culture fishes on these diets. Results showed that larvae and juveniles of B. xanthopterus had accepted the dry food and showed a good survival and growth rates.